2023
DOI: 10.1021/acs.orglett.3c01258
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Atom Transfer Enables the (5+1) Annulation Reaction to Access Aminoisoquinolines

Abstract: Herein, a catalytic synthetic transformation offering a series of -NH 2 group-bearing aminoisoquinolines with moderate to good yields has been showcased. Interestingly, the nitrogen atom of the isoquinoline ring is coming from the reaction medium upon metal-assisted C�N bond cleavage. Moreover, this (5+1) annulation reaction shows broad substrate variation. Furthermore, the derivatization of the isoquinoline core via functional group interconversions and mechanistic studies to identify the reaction intermediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Interestingly, 2-alkynylarylnitriles which could be accessed easily are suitable substrates for accessing various aryl-fused N -heterocycles . We have recently shown that such types of alkynes are excellent starting precursors to access aminoisoquinolines upon reaction with nitrile solvent . During this study, we realized that the C–C triple bond and −CN group could be activated by the metal catalyst toward the nucleophilic addition in a sequential manner.…”
mentioning
confidence: 99%
“…Interestingly, 2-alkynylarylnitriles which could be accessed easily are suitable substrates for accessing various aryl-fused N -heterocycles . We have recently shown that such types of alkynes are excellent starting precursors to access aminoisoquinolines upon reaction with nitrile solvent . During this study, we realized that the C–C triple bond and −CN group could be activated by the metal catalyst toward the nucleophilic addition in a sequential manner.…”
mentioning
confidence: 99%